2008
DOI: 10.1016/j.ccr.2008.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Significance of CD90+ Cancer Stem Cells in Human Liver Cancer

Abstract: This study characterized cancer stem cells (CSCs) in hepatocellular carcinoma (HCC) cell lines, tumor specimens, and blood samples. The CD90+ cells, but not the CD90(-) cells, from HCC cell lines displayed tumorigenic capacity. All the tumor specimens and 91.6% of blood samples from liver cancer patients bore the CD45(-)CD90+ population, which could generate tumor nodules in immunodeficient mice. The CD90+CD44+ cells demonstrated a more aggressive phenotype than the CD90+CD44(-) counterpart and formed metastat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
860
3
13

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,083 publications
(916 citation statements)
references
References 54 publications
(52 reference statements)
25
860
3
13
Order By: Relevance
“…This suggests that CD90 may not be the single marker representing the CSCs of all gastric cancers, owing to the heterogeneity of the gastric cancers, as well as antecede evidence from other studies (Bowles and Benjamin, 2001;Takaishi et al, 2008). A similar multimarker hypothesis has been suggested for CSCs in breast, liver and pancreatic cancers (Al-Hajj et al, 2003;Li et al, 2007;Yang et al, 2008). ERBB2 overexpression could also contribute to the difference in the tumorigenicity of the CD90 þ cells isolated from different primary tumor models.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…This suggests that CD90 may not be the single marker representing the CSCs of all gastric cancers, owing to the heterogeneity of the gastric cancers, as well as antecede evidence from other studies (Bowles and Benjamin, 2001;Takaishi et al, 2008). A similar multimarker hypothesis has been suggested for CSCs in breast, liver and pancreatic cancers (Al-Hajj et al, 2003;Li et al, 2007;Yang et al, 2008). ERBB2 overexpression could also contribute to the difference in the tumorigenicity of the CD90 þ cells isolated from different primary tumor models.…”
Section: Discussionmentioning
confidence: 81%
“…Several studies have also identified Notch1 and ALDH1 as markers in both normal and malignant stem and progenitor cells (Dontu et al, 2004;Matsui et al, 2004;Ginestier et al, 2007). Yang et al (2008) first suggested CD90 to be a potential marker for liver CSCs. Interestingly, in addition to CD90 being highly enriched in cells cultured under sphere conditions, the percentage of CD90 þ cells in the population correlated closely with the tumorigenicity of the gastric primary tumor models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies demonstrated that the CD90 marker was expressed on hepatic stem/ progenitor cells during liver development (33) and in a stem cell population from human adult liver (34,35). In cancer, Yang et al (36) found that CD90 expression correlated with the tumorigenic potential of hepatocellular carcinoma cell lines and suggested CD90 as a putative marker for liver CSCs. Furthermore, Liu et al (37) demonstrated that CD133 1 glioblastoma CSCs from primary cultures presented high levels of CD90 mRNA and were resistant to several chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Mishra and colleagues [28] have suggested that HCC CSCs are descendents of normal parenchymal stem cells that have lost sensitivity to the inhibitory growth effects of TGFβ, while cell selection based on Thy-1 (CD90), a disputed marker of oval cells (see Table 2), in combination with CD44, has also produced cells with aggressive tumorigenic potential [160,161]. It remains to be seen how much overlap there is between these various markers, or whether there is a 'one-fits-all' marker for CSCs in HCC and indeed in other tumour types as well.…”
Section: Mr Alison Et Almentioning
confidence: 99%